Menakar Makna Adil Dalam Keluaga Berpoligini: Perbandingan Pandangan Antara Prof. Dr, Tm. Hasbi Ash-Shiddiqy Dan Prof. Dr. Hamka - Samheri, Samheri; Mawaddah, Mawaddah (International Conference on Islamic Studies, 2022)
In Islamic shari'ah there are two forms of marriage, namely polygamy and monogamy, of which polygamy is the marriage of a man to several women, commonly called "one husband multy wife", and monogamy is an ideal marriage that all women and men want man. Talking about the problem of polygamy, the thing that gets the most attention and debate is the issue of justice in polygamy, Hamka and Teungku M. Hasbi Ash-Shiddiqy are two figures who have different ideas about fairness in polygamy, even though they depart from the same passage namely the Qur'an . In this study, researchers used qualitative research with the type of research used was library research. The data collection method is based on primary and secondary data, and the data analysis is deductive and inductive, while the data processing uses the comparative method. The method the writer uses to describe and analyze the thinking of Hamka and Teungku M. Hasbi Ash-Shiddiqy which includes the concept of fairness in polygamy. From the research conducted, it can be concluded first, that the concept of fairness in polygamy according to Hamka for someone who wants to practice polygamy must be in a state of healthy mind arising from faith and piety. If you are polygamous, a man must be fair, both physically and mentally, but in matters of feelings and affection someone will not be able to be fair. Whereas Teungku M. Hasbi Ash-Shiddiqy bapatapat, polygamy is permissible when in an emergency, that is, if you believe you will do justice, even if someone cannot do justice in feelings and affections that are inner, then that is forgiven. Second, there are factors in equality and differences in the interpretations of the two figures. Among the equations is in the field of methods of interpretation, presentation of interpretations, forms of interpretation and legal basis in polygamy. While the differences between the two figures differ in terms of usage in terms of interpretation, breadth of explanation, background of interpretation and interpretation in QS. Al-Nisa '[4]: 129.